(untitled) (Research, Society and Development, 2021)
Over the past few years, several advances have taken place in transfusion medicine, as well as the development of laboratory techniques used in the serological screening of blood donors, aiming to minimize the transmission of infectious diseases. The importance of detecting total anti-HBc aims to aid in the differential diagnosis of hepatitis, following hepatitis B virus (HBV) infection together with other viral markers, being used in blood banks as a screening test for blood donors, showing efficacy in detecting prior contact with HBV during the “negative window” of HBV. The aim of this study was to evaluate the serological profile for hepatitis B (total anti-HBc) in blood donation candidates in a region of northeastern Brazil. A cross-sectional study was carried out, of qualitative approach, with the computerization system of the entire blood donation cycle, with retrospective data and categorized according to sex, age, location, level of education and risk behavior, having as target population candidates for blood donation in the period from January 2016 to December 2020. Of the 136,652 candidates for donation, reactivity to total anti-HBc was observed in 2.69% (N=3,681). There was greater reactivity to total anti-HBc among male candidates 2.70% (n=2,912) and aged between 29 and 39 years, with 54.9% (n=2,024) living in the interior of the state and one total of 0.91% (n=1,247) with incomplete elementary school. Clinical, laboratory and serological pre-screening for the hepatitis B virus in blood donation candidates is a safety protocol for the transfusion procedure. Aiming to increase the reduction of the risks of contamination and loss of supplies used for the donation, it is necessary to mobilize vaccination campaigns for the hepatitis B virus, and for all those who apply to donate blood at Blood Centers.